2016
DOI: 10.1002/adma.201603253
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Ionic Iridium(III) Complexes for Organic Electronic Devices

Abstract: Ionic iridium(III) complexes are emerging with great promise for organic electronic devices, owing to their unique features such as ease of molecular design and synthesis, excellent photophysical properties, superior redox stability, and highly efficient emissions of virtually all colors. Here, recent progress on new material design, regarding photo- and electroluminescence is highlighted, including several interesting topics such as: i) color-tuning strategies of cationic iridium(III) complexes, ii) widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
168
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(172 citation statements)
references
References 263 publications
(612 reference statements)
4
168
0
Order By: Relevance
“…[35][36][37][38][39][40] However,i TMCs were deemed hard to evaporate due to their intrinsici onic nature and henceo nly appliedf or OLEDs with solution-processed rather than vacuum-deposited emissive material layers (EMLs), [41][42][43][44][45][46][47][48][49][50][51] until Wong et al and Zhang et al successively reported sublimable cationic iridium(III) complexes with large-sized ligands chelated to the iridium core. [54][55][56][57][58] Herein, we further develop as eries of four novel sublimable cationic iridium(III) complexesb earing an imidazole-type ancillary ligand and tetraphenylborate-type negative counter-ions, investigate their photophysical, electrochemical and thermal characteristics, produceh igh-performance yellow and orange electroluminescence,therefore open up the possibility of using iTMCsa salarge family of new phosphorescent emittersi n state-of-the-art vacuum-deposited OLEDs. [54][55][56][57][58] Herein, we further develop as eries of four novel sublimable cationic iridium(III) complexesb earing an imidazole-type ancillary ligand and tetraphenylborate-type negative counter-ions, investigate their photophysical, electrochemical and thermal characteristics, produceh igh-performance yellow and orange electroluminescence,therefore open up the possibility of using iTMCsa salarge family of new phosphorescent emittersi n state-of-the-art vacuum-deposited OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40] However,i TMCs were deemed hard to evaporate due to their intrinsici onic nature and henceo nly appliedf or OLEDs with solution-processed rather than vacuum-deposited emissive material layers (EMLs), [41][42][43][44][45][46][47][48][49][50][51] until Wong et al and Zhang et al successively reported sublimable cationic iridium(III) complexes with large-sized ligands chelated to the iridium core. [54][55][56][57][58] Herein, we further develop as eries of four novel sublimable cationic iridium(III) complexesb earing an imidazole-type ancillary ligand and tetraphenylborate-type negative counter-ions, investigate their photophysical, electrochemical and thermal characteristics, produceh igh-performance yellow and orange electroluminescence,therefore open up the possibility of using iTMCsa salarge family of new phosphorescent emittersi n state-of-the-art vacuum-deposited OLEDs. [54][55][56][57][58] Herein, we further develop as eries of four novel sublimable cationic iridium(III) complexesb earing an imidazole-type ancillary ligand and tetraphenylborate-type negative counter-ions, investigate their photophysical, electrochemical and thermal characteristics, produceh igh-performance yellow and orange electroluminescence,therefore open up the possibility of using iTMCsa salarge family of new phosphorescent emittersi n state-of-the-art vacuum-deposited OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a wide variety of complexes has been designed and used to manufacture LEC devices covering the whole visible spectrum, 16,17,18,19 with high efficiencies, 20,21,22 top lifetimes, 23,24,25 and short turnon times. 26,27,28 However, it is still to be found a complex that allows the fabrication of a device that reunites all those characteristics and becomes suitable for real-life lighting applications.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, an Ir III complex consists of an Ir center and three bidentate ligands, connecting to the Ir atom through C or N. [15] Thus, organoboron groups can be introduced into the different ligands, or an organoboron group itself can even act as a chelating unit. The photophysical properties (including emission colors and quantum yields) of Ir III complexes can be manipulated through the organoboron groups involved in the ligands.…”
Section: Complexesmentioning
confidence: 99%